2016
DOI: 10.1021/acs.est.5b04893
|View full text |Cite
|
Sign up to set email alerts
|

Balancing the Budget: Accounting for Glucocorticoid Bioactivity and Fate during Water Treatment

Abstract: Numerous studies have identified the presence and bioactivity of glucocorticoid receptor (GR) active substances in water; however, the identification and activity-balance of GR compounds remained elusive. This study determined the occurrence and attenuation of GR bioactivity and closed the balance by determining those substances responsible. The observed in vitro GR activity ranged from 39 to 155 ng dexamethasone-equivalent/L (ng Dex-EQ/L) in the secondary effluents of four wastewater treatment plants. Monochr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
84
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(95 citation statements)
references
References 42 publications
11
84
0
Order By: Relevance
“…Overall, our findings identified target compounds as the main contributors to the estrogen and glucocorticoid agonistic activity in the effluent extracts. These observations agree with earlier reports in which the synthetic glucocorticoids clobetasol propionate and fluticasone propionate significantly contributed to the glucocorticoid activity in WWTP effluents (Macikova et al ; Suzuki et al ; Jia et al ). Steroidal estrogens are well‐known major contributors of estrogenic activity in urban WWTP effluents (reviewed by Jarosova et al ), as again confirmed at the studied site.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Overall, our findings identified target compounds as the main contributors to the estrogen and glucocorticoid agonistic activity in the effluent extracts. These observations agree with earlier reports in which the synthetic glucocorticoids clobetasol propionate and fluticasone propionate significantly contributed to the glucocorticoid activity in WWTP effluents (Macikova et al ; Suzuki et al ; Jia et al ). Steroidal estrogens are well‐known major contributors of estrogenic activity in urban WWTP effluents (reviewed by Jarosova et al ), as again confirmed at the studied site.…”
Section: Resultssupporting
confidence: 93%
“…Effect‐based tools have been proposed in water quality assessment because they are considered integrative techniques for the detection of bioactive compounds (Eggen et al ; Altenburger et al ). A variety of in vitro receptor‐based assays currently exists for the assessment of EDCs and many studies have reported their effectiveness for water quality assessment (i.e., for monitoring the endocrine‐disrupting potential of WWTP effluents; Schriks et al ; Creusot et al ; Macikova et al ; Jia et al ). Mechanism‐based in vivo assays using transgenic fish embryos that allow sensitive detection of EDCs within a living organism have also been recently developed (Brion et al ; Gorelick et al ).…”
Section: Introductionmentioning
confidence: 99%
“…Both progestogens and glucocorticoids act through binding to a wide range of receptors including progesterone (PR), estrogen (ER), androgen (AR), glucocorticoid (GR), and mineralocorticoid (MR) receptors (Kumar et al 2015). The presence of progestogens and glucocorticoids in the environment can be detected by chemical trace analysis (Schriks et al 2010;Ammann et al 2014;Jia et al 2016;Shen et al 2018) or biologically via PR and GR binding using a variety of reporter gene assays (Creusot et al 2014;Jia et al 2015;Wangmo et al 2018). Because GR and PR ligands are rarely monitored (in contrast to ERs), only limited information is available on the occurrence and concentrations of these compounds in the environment (Fent 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In 2016 the number of prescriptions for prednisolone and dexamethasone in the United States exceeded 4 and 1 million, respectively (Kane, 2018). Furthermore, pharmaceutical glucocorticoids have also been detected in wastewater samples worldwide (Schriks et al 2010;Kolkman et al 2013;Macikova et al 2014;Suzuki et al 2015;Jia et al 2016). Humans also endogenously secrete a glucocorticoid called cortisol in response to stress.…”
Section: Discussionmentioning
confidence: 99%